2021
DOI: 10.1021/jacs.1c05551
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of a Triazolylferrocenyl Dendrimer in Water Yields Nontraditional Intrinsic Green Fluorescent Vesosomes for Nanotheranostic Applications

Abstract: The promising field of nanomedicine stimulates a continuous search for multifunctional nanotheranostic systems for imaging and drug delivery. Herein, we demonstrate that application of supramolecular chemistry’s concepts in dendritic assemblies can enable the formation of advanced dendrimer-based nanotheranostic devices. A dendrimer bearing 81 triazolylferrocenyl terminal groups adopts a more compact shell-like structure in polar solvents with the ferrocenyl peripheral groups backfolding toward the hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Our group has reported a series of folate derivatives containing ferrocenyl groups and it was found that the folate bearing a triazole group conjugated to the ferrocenyl unit was the most active compound against cancer cells, being the lowest IC 50 value obtained against MCF‐7 cells (21.7 μM) [11] . Moreover, the cytotoxicity of self‐assembled structures of a dendrimer bearing eighty one triazolylferrocenyl groups with nontraditional intrinsic fluorescence was also evaluated [13] . These assemblies were able to penetrate the intracellular medium of MCF‐7 cells, changing cells′ morphology, and exhibiting IC 50 of 124 μM of Fc groups or 1.5 μM of dendrimer after 48 h of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group has reported a series of folate derivatives containing ferrocenyl groups and it was found that the folate bearing a triazole group conjugated to the ferrocenyl unit was the most active compound against cancer cells, being the lowest IC 50 value obtained against MCF‐7 cells (21.7 μM) [11] . Moreover, the cytotoxicity of self‐assembled structures of a dendrimer bearing eighty one triazolylferrocenyl groups with nontraditional intrinsic fluorescence was also evaluated [13] . These assemblies were able to penetrate the intracellular medium of MCF‐7 cells, changing cells′ morphology, and exhibiting IC 50 of 124 μM of Fc groups or 1.5 μM of dendrimer after 48 h of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Conjugation of ferrocenyl units to dendrimers have resulted in redox‐active macromolecular systems with interesting properties to many fields of science [12] . Recently, we have reported that a hydrophobic dendrimer bearing 81 triazolylferrocenyl termini self‐assembled into large vesosomes in aqueous medium [13] . These vesosomes emit green nontraditional intrinsic fluorescence (NTIL) and present activity against cancer cells [13] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DDS is a system that delivers the drugs “in a minimum amount”, “at the right time”, and “to the right place”. Polymer micelles [ 5 , 6 ], dendrimers [ 7 , 8 , 9 ], hydrogels [ 10 , 11 , 12 , 13 ], and mesoporous nanoparticles [ 14 , 15 , 16 ] have been reported as DDS carriers. In addition, vesicles have been used for DDS carriers.…”
Section: Introductionmentioning
confidence: 99%